Modelling in transport phenomena a conceptual approach - Tosun, Ismail (Amsterdam ; Boston : Elsevier, 2002)
Modelling in Transport Phenomena is intended as an introduction to Transport Phenomena courses. Although it is written for students majoring in chemical engineering, it can also be used as a reference or a supplementary text in environmental, mechanical, petroleum and civil engineering courses. It has been designed in order to help students understand basic concepts that are usually difficult to grasp. These concepts are clearly explained within this text and their applications to fluid flow, heat transfer, mass transfer, chemical reaction engineering and thermodynamics are presented through a.
Front Cover; Modelling in Transport Phenomena: A Conceptual Approach; Copyright Page; Preface; Contents; Chapter 1. Introduction; Chapter 2. Molecular and Convective Transport; Chapter 3. Interphase Transport and Transfer Coefficients; Chapter 4. Evaluation of Transfer Coefficients: Engineering Correlations; Chapter 5. Rate of Generation in Momentum, Energy and Mass Transfer; Chapter 6. Steady-State Macroscopic Balances; Chapter 7. Unsteady-State Macroscopic Balances; Chapter 8. Steady-State Microscopic Balances Without Generation; Chapter 9. Steady-State Microscopic Balances With Generation
Includes bibliographical references and index.
Keywords: Transport theory; Chemical engineering; Electronic books